2014
DOI: 10.2475/07.2014.01
|View full text |Cite
|
Sign up to set email alerts
|

Taconian orogenesis, sedimentation and magmatism in the southern Quebec-northern Vermont Appalachians: Stratigraphic and detrital mineral record of Iapetan suturing

Abstract: International audienceCambrian-Ordovician units of the southern Quebec Appalachians oceanic domain include obducted ophiolites and an overlying syncollisional sedimentary basin represented by the Saint-Daniel Mélange and flysch units of the Magog Group. These terrains were thrust onto the Laurentian continental margin during the Taconian orogeny and are unconformably overlain by Silurian-Devonian successor basins. This contribution presents and discusses new stratigraphic data acquired in the oceanic domain, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 88 publications
(74 reference statements)
0
4
0
1
Order By: Relevance
“…With respect to the latter, Whitehead et al (1996) demonstrated via 40 Ar/ 39 Ar geochronology that hornblende, muscovite, and K-feldspar crystals in rocks from the Canadian Appalachians in southeastern Qu ebec show thermal signals around~463 Ma related to the Ordovician Taconic orogeny (c. 480-445 Ma; e.g., St. Julien and Hubert 1975;De Souza et al 2014). Tremblay and Castonguay (2002) also reported 40 Ar/ 39 Ar ages of~469-461 Ma, in addition to 40 Ar/ 39 Ar ages of~430-410 Ma, for the domain south of Qu ebec City, reflecting the Salinian orogeny in the Late Silurian and Early Devonian (e.g., Cawood et al 1995;Van Staal et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the latter, Whitehead et al (1996) demonstrated via 40 Ar/ 39 Ar geochronology that hornblende, muscovite, and K-feldspar crystals in rocks from the Canadian Appalachians in southeastern Qu ebec show thermal signals around~463 Ma related to the Ordovician Taconic orogeny (c. 480-445 Ma; e.g., St. Julien and Hubert 1975;De Souza et al 2014). Tremblay and Castonguay (2002) also reported 40 Ar/ 39 Ar ages of~469-461 Ma, in addition to 40 Ar/ 39 Ar ages of~430-410 Ma, for the domain south of Qu ebec City, reflecting the Salinian orogeny in the Late Silurian and Early Devonian (e.g., Cawood et al 1995;Van Staal et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This suture zone extends along the Appalachians to western Newfoundland, where the Bay of Islands Complex, a klippe of the Dunnage zone, is the most complete ophiolite of the orogeny (Cawood and Suhr, 1992). The Dunnage zone represents the Ordovician oceanic basin related to the Iapetus ocean and located outboard of the continental passive margin of Laurentia defining the Humber zone (Williams, 1979;De Souza et al, 2014). The Mont Albert ophiolite and its sole overlay unconformably the Schick-Schock volcanic flows and pyroclastics metamorphosed to lower greenschist facies that appear in the internal Humber zone in recent publications (reviewed in Tremblay and Pinet, 2016), although Lux (1986) suggested they are part of the Dunnage zone.…”
Section: Structural Organization and Radiometric Constraintsmentioning
confidence: 99%
“…No detrital zircon data are available from pre-accretion deposits in these northern Maine inliers, but numerous data sets from the Connecticut Valley -Gaspé trough to the north, and the Central Maine trough to the south, show predominant Laurentia-derived populations (with large peaks at ~0.95 -1.2 Ga) (De Souza et al, 2014;Perrot et al, 2017Perrot et al, , 2018.…”
Section: Northern Maine Inliersmentioning
confidence: 99%